The Effect of Debt Management, Budgeting Policy, and Green Investment on Financial Growth of Information Technology Companies in West Java - Loso Judijanto; Adih Supriadi; Tera Lesmana (Westscience Press, 2024)
The study investigates the effect of debt management, budgeting policy, and green investment on the financial growth of information technology companies in West Java. Utilizing a quantitative approach, the research collected data from 190 IT companies using a Likert scale questionnaire (1-5), analyzing the results through Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings highlight the significant impact of effective debt management and sound budgeting policies in promoting financial growth. Additionally, green investment initiatives play a crucial role in enhancing the sustainability and long-term profitability of these companies. The study provides valuable insights for IT companies seeking to balance financial stability and environmental responsibility.